Professional C++ - Solter, Nicholas 1977-; Kleper, Scott 1977- (Wiley, 2005)
"Geared to experienced C++ developers who may not be familiar with the more advanced features of the language, and therefore are not using it to its full capabilities. Teaches programmers how to think in C++ -- that is, how to design effective solutions that maximize the power of the language. The authors drill down into this notoriously complex language, explaining poorly understood elements of the C++ feature set as well as common pitfalls to avoid. Contains several in-depth case studies with working code that's been tested on Windows, Linux, and Solaris platforms."--Publisher's description
Includes bibliographical references (pages 803-811) and index. - Print version record
Keywords: C++ (Computer program language); C++ (Langage de programmation); COMPUTERS; Programming Languages; C♯; COMPUTERS; Programming Languages; Java; COMPUTERS; Programming Languages; Pascal